Male-to-Female Gender-Affirming Surgery: 20-Year Review of Technique and Surgical Results - Moisés da Silva, Gabriel Veber; Lobato, Maria Inês Rodrigues; Silva, Dhiordan Cardoso; Schwarz, Karine; Fontanari, Anna Martha Vaitses; Costa, Angelo Brandelli; Tavares, Patric Machado; Gorgen, Antonio Rebello Horta; Cabral, Renan Desimon; Rosito, Tiago Elias (Frontiers in Surgery, 2021)
Purpose: Gender dysphoria (GD) is an incompatibility between biological sex and personal gender identity; individuals harbor an unalterable conviction that they were born in the wrong body, which causes personal suffering. In this context, surgery is imperative to achieve a successful gender transition and plays a key role in alleviating the associated psychological discomfort. In the current study, a retrospective cohort, we report the 20-years outcomes of the gender-affirming surgery performed at a single Brazilian university center, examining demographic data, intra and postoperative complications. During this period, 214 patients underwent penile inversion vaginoplasty. Results: results demonstrate that the average age at the time of surgery was 32.2 years (range, 18 to 61 years); the average of operative time was 3.3 hours (range, 2 to 5 hours); the average duration of hormone therapy before surgery was 12 years (range, 1-39). The most commons minor postoperative complications were granulation tissue (20.5 percent) and introital stricture of the neovagina (15.4 percent) and the major complications included urethral meatus stenosis (20.5 percent) and hematoma/excessive bleeding (8.9 percent). A total of 36 patients (16.8 percent) underwent some form of reoperation. One hundred eighty-one (85 percent) patients in our series were able to have regular sexual intercourse, and no individual regretted having undergone GAS. Conclusions: findings confirm that it is a safety procedure, with a low incidence of serious complications. Otherwise, in our series, there were a high level of functionality of the neovagina, as well as subjective personal satisfaction.